2017
DOI: 10.3389/fmicb.2017.00050
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability and the Effect of Transgenerational Transfer on Fecal Microbiota Structure in a Long Distance Migratory Bird

Abstract: Animal bodies are inhabited by a taxonomically and functionally diverse community of symbiotic and commensal microorganisms. From an ecological and evolutionary perspective, inter-individual variation in host-associated microbiota contributes to physiological and immune system variation. As such, host-associated microbiota may be considered an integral part of the host’s phenotype, serving as a substrate for natural selection. This assumes that host-associated microbiota exhibits high temporal stability, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
95
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 123 publications
(184 reference statements)
15
95
2
Order By: Relevance
“…The phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes dominated barn swallow CMs, consistently with the results on populations from the Czech Republic, which are~580 km far from our study area, where a high abundance of the phylum Tenericutes was also reported (Kreisinger et al 2015(Kreisinger et al , 2017. Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes dominated barn swallow CMs, consistently with the results on populations from the Czech Republic, which are~580 km far from our study area, where a high abundance of the phylum Tenericutes was also reported (Kreisinger et al 2015(Kreisinger et al , 2017. Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Proteobacteria and Firmicutes are common in the gastrointestinal trait of birds (Godoy-Vitorino et al 2012;Waite et al 2012;Waite & Taylor 2015). A more detailed description of the bacterial community at a lower taxonomic level showed that the most abundant genera differed from those observed in previous studies: the genera Ralstonia, Pseudomonas, Aeribacillus, and Arenimonas were abundant in our samples, while they were not found in the two previous studies in the Czech Republic (Kreisinger et al 2015(Kreisinger et al , 2017. Ralstonia spp.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations